The Main Approaches to the Concept and Types of Charges in the Russian Criminal Process - A. V. Bogdanova (Теоретическая и прикладная юриспруденция)
The subject of this study is the institute of prosecution in domestic criminal proceedings. In the first part of the article, the author explores the concept of accusation. Approaches are considered in which the accusation was identified both with a criminal suit and with criminal prosecution. The second part of the presented work is devoted to the types of charges and the criteria for their differentiation. A summary analysis of the positions of modern, Soviet and pre-revolutionary researchers of law on this issue is given. Various types of charges are considered depending on the subject entitled to its implementation. Particular attention is paid to the so-called public prosecution, which was supported by citizens who were not endowed with this right ex officio. Based on the study, the author comes to the conclusion that the adversarial model of the criminal process is characterized by the presence of various types of charges, as well as various subjects entitled to its implementation. At the moment, in the Russian criminal process there is a so-called “prosecutor’s monopoly” on the prosecution, which is somewhat limited by the presence of a private prosecution. However, a small number of offenses classified as private prosecution, as well as the number of criminal cases in this category considered by the courts, does not change the existing paradigm. Thus, the existing procedure does not fully correspond to the adversarial model of the criminal process.